Collateral Circulation and Outcome in Atherosclerotic Versus Cardioembolic Cerebral Large Vessel Occlusion. Issue 12 (December 2019) - Guglielmi, Valeria; LeCouffe, Natalie E.; Zinkstok, Sanne M.; Compagne, Kars C.J.; Eker, Reyhan; Treurniet, Kilian M.; Tolhuisen, Manon. L.; van der Worp, H. Bart; Jansen, Ivo G.H.; van Oostenbrugge, Robert J.; Marquering, Henk A.; Dippel, Diederik W.J.; et al.
Abstract : Background and Purpose—: Due to chronic hypoperfusion, cervical atherosclerosis may promote cerebral collateral circulation. We hypothesized that patients with ischemic stroke due to cervical carotid atherosclerosis have a more extensive collateral circulation and better outcomes than patients with cardioembolism. We tested this hypothesis in a population of patients who underwent endovascular treatment for large vessel occlusion. Methods—: From the MR-CLEAN Registry (Multicenter Randomized Controlled Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands), we selected consecutive adult endovascular treatment patients (March 2014 to June 2016) with acute ischemic stroke due to anterior circulation large vessel occlusion and compared patients with cervical carotid artery stenosis >50% to those with cardioembolic etiology. The primary outcome was collateral score, graded on a 4-point scale. Secondary outcomes included the modified Rankin Scale (mRS) score and mortality at 90 days. We performed multivariable regression analyses and adjusted for potential confounders. Results—: Of 1627 patients in the Registry, 190 patients with cervical carotid atherosclerosis and 476 with cardioembolism were included. Patients with cervical carotid atherosclerosis were younger (median 69 versus 76 years, P <0.001), more often male (67% versus 47%, P <0.001), more often had an internal carotid artery terminus occlusion (33% versus 18%, P <0.001), and a lower prestroke mRS (mRS score, 0–2; 96% versus 85%, P <0.001), than patients with cardioembolism. Stroke due to cervical carotid atherosclerosis was associated with higher collateral score (adjusted common odds ratio, 1.67 [95% CI, 1.17–2.39]) and lower median mRS at 90 days (adjusted common odds ratio, 1.45 [95% CI, 1.03–2.05]) compared with cardioembolic stroke. There was no statistically significant difference in proportion of mRS 0–2 (aOR, 1.36 [95% CI, 0.90–2.07]) or mortality at 90 days (aOR, 0.80 [95% CI, 0.48–1.34]). Conclusions—: Patients with stroke due to cervical carotid atherosclerosis had a more extensive cerebral collateral circulation and a slightly better median mRS at 90 days than patients with cardioembolic stroke. Abstract : Supplemental Digital Content is available in the text.